Hybrid Adhesive Made from Citric Acid and Sucrose for Particleboard Composed of Sengon (Paraserianthes falcataria (L.) Nielsen) Veener By-Products and Sorghum Stalk (Universitas Negeri Semarang, 2022)
Particleboard is a product of wood technology engineering made of wood particles and other lignocellulosic materials which are bonded with synthetic adhesives. As an information, utilization of natural adhesive for particleboard is still limited. This study aimed to determine the influence of hybrid adhesive made from citric acid and sucrose for particleboard properties composed of Sengon veener by-products and sorghum stalk. The hybrid adhesive content used was 15% of citric acid and 25% of sucrose that calculated from the dry weight of particles. The mixture ratio of hybrid adhesive for both citric acid and sucrose were 100:0, 75:25, 50:50, 25:75, and 0:100 (% w/w). The manufacture of particleboard was set on target density of 0.8 g/cm3 under a press temperature of 200o C for 10 minutes. Mostly, the properties of particleboard were shown to be affected by the adhesive content and composition ratio between citric acid and sucrose and met the Japan Industrial Standard A 5908:2003. The value of modulus of elasticity, modulus of rupture, internal bond, and screw holding were ranged about 1.21-3.49 GPa, 12.77-20.24 MPa, 0.18-0.90 MPa and 167.71-321.27 N. Particleboard with 15% of citric acid content and the mixture ratio both citric acid and sucrose of 50:50 has the best physical and mechanical properties and met the requirement of Japan Industrial Standard A 5908:2003.